PERLINDUNGAN TERHADAP ORANG-ORANG DALAM DAERAH KONFLIK BERSENJATA MENURUT HUKUM HUMANITER INTERNASIONAL - Adwani Adwani (Jurnal Dinamika Hukum, 2012)
Persons that involved in an armed conflict are protected by law which regulated in Article 13 of Geneva Convention 1949. There are some persons who receive protection such as combatants, militia and levee en maase and civilians as a matter of law, however, the protection itself has not been fully implemented. This article aims to discuss persons who receive protection whether the persons involve in an armed conflict or not. In principle, persons who involve in an armed conflict must protect the combatants who took direct participation when the combatants are wounded and hostile. However, the protection are not implemented accordingly since they often receive violence attacks. Furthermore, civilians often became victim of attack that classified as inhuman treatment.   Keywords: Protected, proctected persons, armed conflict